Preliminary Efficacy of Face-to-Face, Telerehabilitation, and Home Program–Based Task-Oriented Circuit Training on the Cognitive and Motor Functions of Older Adults: A Single-Blind Randomized Feasibility Study. - Turkmen, Ceyhun; Karakus, Aysenur; Yilmaz, Seyma; Sengül, Feyza; Sigirtmac, Ilkem Ceren (American Journal of Occupational Therapy)
Importance: Task-oriented circuit training (TOCT) is a structured intervention to enhance older adults' cognitive and motor functions. However, the feasibility and effectiveness of TOCT delivered through face-to-face, telerehabilitation, and home-based methods remain unclear. Objective: To evaluate the feasibility and preliminary efficacy of TOCT delivered through different modalities on cognitive and motor functions in older adults. Design: A randomized feasibility study. Setting: A state-operated skilled nursing facility in Turkey that provides daily-living assistance with on-site medical coverage for emergencies. Participants: Fifty-four older adults (ages ≥65 yr). Inclusion criteria included Mini-Mental State Examination (MMSE) scores >18. Adults with moderate or severe impairment (MMSE scores ≤18) were excluded. Intervention: Participants were randomly assigned to face-to-face, telerehabilitation, or home-based TOCT. They engaged in structured TOCT activities to improve joint protection, memory, attention, and fine motor skills. Sessions were delivered for 60 min daily for 2 wk. Pre- and postintervention assessments were conducted. Outcomes and Measures: Assessments included the MMSE, the Montreal Cognitive Assessment, the Nine-Hole Peg Test, and subscales of the 36-Item Short Form Health Survey. Results: Face-to-face TOCT showed the greatest cognitive improvements (MMSE: d = 1.52), whereas telerehabilitation improved energy and vitality levels (d = 0.91) and social functioning (d = 1.41). Home-based training showed the smallest improvements overall. Conclusions and Relevance: TOCT through face-to-face and telerehabilitation methods effectively improved cognitive and motor functions. Face-to-face training yielded the greatest cognitive benefits, whereas telerehabilitation enhanced quality of life. Home-based interventions had limited impact. Future research should explore long-term outcomes and refine home-based programs. Plain-Language Summary: As people age, cognitive and motor skills decline, making daily activities harder. This study examined task-oriented circuit training, a structured program delivered through face-to-face, telerehabilitation, and home-based methods. Face-to-face training showed the greatest cognitive improvements, whereas telerehabilitation enhanced energy and vitality levels and social participation. Home-based programs had minimal benefits. These findings support remote task-oriented circuit training as a viable option, although further research is needed to improve home-based interventions. This study examined task-oriented circuit training, a structured program delivered through face-to-face, telerehabilitation, and home-based methods.